2015
DOI: 10.1177/1553350615585421
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Magnetometer for Sentinel Lymph Node Mapping Designed for Video-Assisted Thoracic Surgery in Non–Small Cell Lung Cancer

Abstract: The new VATS-compatible magnetometer appears to have substantial advantages over techniques using a radioisotope and our earlier magnetometer, as it can be inserted through the small VATS port site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Meng et al (63) suggested that if MRI could accurately diagnose axillary lymph node metastases in early stage breast cancer, the most cost-effective strategy was to replace sentinel lymph node biopsy with axillary MRI. Detection of sentinel lymph nodes with SPIO can be done by a simple hand-hold probe ( Figure 3) (64)(65)(66)(67). A number of studies with the combination of Sienna plus ® and SentiMag ® (Endomagentics Ltd) have been reported.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%
“…Meng et al (63) suggested that if MRI could accurately diagnose axillary lymph node metastases in early stage breast cancer, the most cost-effective strategy was to replace sentinel lymph node biopsy with axillary MRI. Detection of sentinel lymph nodes with SPIO can be done by a simple hand-hold probe ( Figure 3) (64)(65)(66)(67). A number of studies with the combination of Sienna plus ® and SentiMag ® (Endomagentics Ltd) have been reported.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%
“…However, comparing with the standard dual technique, the predefined non-inferiority margin was not reached in the MELAMAG Trial [23]. Furthermore, initial data on the use of magnetometer-guided SLN detection in lung cancer and colorectal cancer were reported [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was shown that SPIONs reach the axillary lymph nodes within minutes after injection into the breast [ 60 ]. To detect SPIONs, several magnetometers have been developed [ 43 , 56 , 64 ].…”
Section: Intraoperative Diagnosis During Surgerymentioning
confidence: 99%